MODELS OF PRESCRIPTION FILLING AND REFILLING SERVICES FOR CHRONIC DISEASE PATIENTS AT COMMUNITY PHARMACIES IN FOREIGN COUNTRIES - Lochid-amnuay, Surasit; Pontom, Durongkorn (Thai Bulletin of Pharmaceutical Sciences, 2023)
Prescription filling and refilling are pharmaceutical services for chronic disease patients that involve a pharmacist providing medication refill services for patients during the period before their next physician appointment. The pharmacist gives advice, monitors drug intake, searches and solves drug-related problems with the prescriber and expands community pharmacist roles. According to data on the services in community pharmacies in foreign countries, including the United Kingdom, Australia, South Korea, the United States, and Germany, it is general practice that each country has similar patterns of service provisions. They use different methods to set a list of reimbursable drugs, set a standard price for reimbursing the drug costs to the pharmacy, determine the professional fee for each service, and collect co-payments from patients. Additionally, information technology is supported to link community pharmacists to the health system, enabling access to necessary service information.